Novel Liquid-Liquid-Solid Microextraction Using Molecularly Imprinted Polymer Monolithic Fibres and its Application to the Extraction of s-Triazine Herbicides from Water Samples - Jun Chen; Lianyang Bai; Li Zhang; Mei Hu; Yuping Zhang (Adsorption Science & Technology, 2014)
A novel method to quickly prepare molecularly imprinted polymer (MIP) monolithic fibres is developed using microwave irradiation. The well-known water-compatibility problem of MIP is overcome by liquid-liquid-solid microextraction (LLSME). The atrazine (ATR) MIP fibre was obtained after silica was etched away with a controlled length of 1 cm, and subsequently characterized by scanning electron microscopy. Main factors affecting the selective extraction, including extraction time, desorption time, extraction and desorption solvents, were investigated for LLSME procedures in detail. The selectivity was also evaluated using the ATR template molecule and its structurally related compounds, including 2-amino-4-methoxy-6-methyl-1,3,5-triazine, terbuthylazine, ametryn and metribuzin pesticides. The extraction ratio of target pesticides in ATR-imprinted polymeric monolithic fibre was increased to more than 10 times than that in non-imprinted polymeric monolithic fibre. The resultant fibres coupled by HPLC were successfully applied to detect ATR and its analogue pesticides with recoveries in the range of 68.3–92.6%. In addition, the LLSME technique was proved to be effective in extracting spiked TRI, ATR, AME and TER in lake water. This method provided a satisfactory solution for the simple, rapid, selective and sensitive pre-treatment of trace herbicides in various aqueous samples. The results demonstrate that the proposed technique could solve the water compatibility problem when the MIP monolithic fibre was exposed directly to a non-polar solvent above the aqueous solution.